Bacterial translocation to mesenteric lymph nodes fueling surgical site infections: evidence, technical challenges and future directions - Simone N. Zwicky; Lara Mordasini; Daniel Spari; Bahtiyar Yilmaz; Guido Beldi (Journal of Translational Medicine)
Abstract Surgical site infections (SSIs) continue to pose a significant healthcare challenge by contributing to longer post-surgical recovery times, greater healthcare costs and higher patient mortality. The traditional understanding of SSIs has focused on the impact of various external origins of contamination or on the importance of intestinal spillage during surgical procedures. However, recent studies highlight the significant contribution of the patient's intestinal microbiota in the onset of SSIs. One possible pathway of infection is translocation of bacteria from the intestines to organs that are typically sterile, such as the mesenteric lymph nodes (MLNs). These secondary lymphoid organs are then potential reservoirs for SSIs. This review summarizes the current data on the incidence and mechanisms of bacterial translocation (BT) to MLNs in the context of a surgical insult and its association with postoperative infectious complications. Data from animal studies discuss how BT to MLNs is driven by factors such as dysbiosis and surgical interventions and is strongly linked to infectious outcomes. Potential translocation pathways including intracellular transit and carrier-independent mechanisms are explored. Similarly, human studies provide evidence that BT to MLNs is a frequent occurrence during abdominal surgery and significantly increases the risk of infectious complications. We further discuss the limitations of current methodologies for studying BT and SSIs and highlight how advanced techniques can provide novel insights into these processes. This review identifies key areas for future research and potential targets for preventative strategies to increase our understanding of the role of the intestinal microbiota in BT to MLNs and its contribution to SSIs.